2021
DOI: 10.3390/cosmetics8030074
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quality Control Method for the Determination of the Refractive Index of Oil-in-Water Creams and Its Correlation with Skin Hydration

Abstract: The sensory properties of cosmetic products can influence consumers’ choice. The accurate correlation of sensory properties, such as skin hydration, with the material properties of the formulation could be desirable. In this study, we aimed to demonstrate a new method for the in vitro measurement of the refractive indices (RIs) of turbid creams. The critical wavelength of each cream was obtained through direct measurement using a sun protection factor (SPF) meter; the wavelength value was then applied in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The refractive index (RI) is a measure used for identification and as a criterion of purity of oils. It is also used as an index of the degree of hydrogenation of the oil 32,33 . The RI of oils depends on their molecular weight, their degree of unsaturation, the chain length of fatty acids, and the degree of conjugation 34 .…”
Section: Sesame Oil Physicochemical Characteristicsmentioning
confidence: 99%
“…The refractive index (RI) is a measure used for identification and as a criterion of purity of oils. It is also used as an index of the degree of hydrogenation of the oil 32,33 . The RI of oils depends on their molecular weight, their degree of unsaturation, the chain length of fatty acids, and the degree of conjugation 34 .…”
Section: Sesame Oil Physicochemical Characteristicsmentioning
confidence: 99%
“…To enable time-and cost-effective quality control testing, assessment methodologies are constantly evolving. In the study conducted by my research group [7] we reported a novel QC method for the determination of refractive indices of creams, using an SPF meter. The RI values then presented the correlation with preliminary skin hydration data after the application of the creams.…”
mentioning
confidence: 99%